Apriori Algorthm Implementation to Determine Product Sales Priority - Anggit Dwi Hartanto; Bobby Candera Lim; Deas Pradana (Universitas Raharja, 2020)
Nowadays there are so many stores that stand where every day you have a transaction on selling goods. Sometimes transactions per day are not small, these many transactions can lead to a buildup of data. However, it is rare for business owners to realize that the data can be processed into various kinds of information which can later be used for the interests of companies and stores. The solution to this can be to use an algorithm that is often used today, namely the Apriori algorithm. The Priori algorithm is one of the data mining techniques used to find high associative patterns between products. The calculation is done by determining the support and confidence between the itemset set in the transaction or also called the association rule function. The test results with a priori algorithm get results in the form of an association rule, one of which is the connection of Oily Skin Clean Wash items -> Eshter Acne Toner with the highest support value of 1.0000. So it is expected that this can be used as a reference in efficient product sales going forward